2016
DOI: 10.1097/01.ogx.0000483239.08585.8d
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection in Pregnant Women in Rio de Janeiro—Preliminary Report

Abstract: BACKGROUND Zika virus (ZIKV) has been linked to neonatal microcephaly. To characterize the spectrum of ZIKV disease in pregnancy, we followed patients in Rio de Janeiro to describe clinical manifestations in mothers and repercussions of acute ZIKV infection in fetuses. METHODS We enrolled pregnant women in whom a rash had developed within the previous 5 days and tested blood and urine specimens for ZIKV by reverse-transcriptase-polymerasechain-reaction assays. We followed the women prospectively and collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
444
4
19

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(476 citation statements)
references
References 14 publications
9
444
4
19
Order By: Relevance
“…12,33 We expect one component of the congenital Zika syndrome to be intrauterine growth restriction; we recorded a high proportion of neonates with microcephaly who were small for gestational age. Brasil and colleagues 7 reported fetal growth restriction in fetuses of mothers who had Zika virus infection during pregnancy. In June, 2016, WHO recommended the use of Intergrowth-21 Size at Birth Standards for identifying neonates with microcephaly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,33 We expect one component of the congenital Zika syndrome to be intrauterine growth restriction; we recorded a high proportion of neonates with microcephaly who were small for gestational age. Brasil and colleagues 7 reported fetal growth restriction in fetuses of mothers who had Zika virus infection during pregnancy. In June, 2016, WHO recommended the use of Intergrowth-21 Size at Birth Standards for identifying neonates with microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…5 Since the hypothesis that the microcephaly epidemic in Brazil is caused by congenital Zika virus infection was fi rst proposed, 6 there has been an accumulation of evidence supporting the association. [7][8][9][10][11][12][13][14][15][16][17] The relation between Zika virus and birth defects is strong enough to be deemed causal, but the argument would be stronger if confi rmed by at least one case-control study and a cohort study. 18 Indeed, the evidence so far comes from case reports, 16 case series, 19,20 modelling studies, 17 and the preliminary report of a cohort study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, physicians and scientists from Brazil and other countries have shown that ZIKV causes a severe congenital disease by infecting the central nervous system of the fetus in all phases of pregnancy. ZIKV is a neurotropic virus, and high viral loads have been found in the nervous tissues of the stillborn children of mothers infected with ZIKV (10) . Information has been collected as fast as possible to help the management of patients, provide the guidance to women in childbearing age and pregnancy, and to control the outbreaks.…”
mentioning
confidence: 99%
“…6 Recent studies suggest that Zika virus infection can cause severe joint damage and genitourinary, cardiac, and digestive complications among aff ected infants. 7 Many could be impaired in less obvious ways, with disabilities appearing later in a child's development.…”
mentioning
confidence: 99%